Turismo étnico y la medicina, conocimiento o artesanía ancestral en la comunidad Juan Montalvo - Palma Parrales, Sanyar María (2019)
Ethnic tourism and the scarce practice of medicine and knowledge or ancestral crafts of indigenous nationalities is a problem that has caused a decline in the cultural identity of ethnic groups. This problem has affected in such a way that in many of the cases it has caused the acculturation of some members of the indigenous communities, that because they relate to people from another culture and because they feel uncomfortable with their own culture, they have adopted different cultural habits. to cultural syncretism. The present investigation, through the application of methods, techniques and instruments, obtained as a result that the scarce practice of ancestral medicine and craft of the Kichwa nationality, is due to the decadence of the cultural identity, this has caused the Kichwa families, do not use the knowledge about medicinal plants that the Yachaks and midwives possess for the cure of diseases, because they prefer to make use of Western medicine. The ancestral crafts of the Kichwa nationality, is characterized by the development of three types of crafts: woven, ceramic and carved, the latter is in danger of extinction, because very few Kichwa families practice it, this is because the members of the community do not pass on the knowledge of artisanal techniques to the new generations.